IDENTIFYING MAP LOCATIONAND MARKERS LINKEDTO THERMOSENSITIVE GENIC MALE STERILITYGENE IN 103S LINE - Hien, Vu; Yoshimura, Atsushi (Tạp chí Khoa học Nông nghiệp Việt Nam, 2024)
The thermosensitive genic male sterile rice line, TGMS 103S, ispopularly used in the rice hybrid seed production in North Viet Nam. It iswell known as the mother line of nationalhybrid rice varieties, such as Vietlai 20 and Vietlai 24. Genes controlling sterility of the TGMS 103S were not determined. The objective of this study was to identify genes controlling f sterility of TGMS 103S by using DNA markers. Phenotypic and genetic analyses wereconducted by using F1and F2population derived from TGMS103S and R20. Linkage groups and the order of markers were determined using MAPMAKER//EXP 3.0.The phenotypic and SSR data were combined for linkage analysis using the MAPMAKER program and a linkage map of specific chromosome region surrounding the tgmsgene was constructed.The result showed that tms-103Sof TGMS 103S was located on chromosome 2 with flanking SSR markers of RM3294, RM6378, RM7575and RM71. These markers couldbe usedfor marker-assisted selection/marker-assisted backcrossing to transfertms-103Sfor developing female parent in two line hybrid rice breeding.